1997
DOI: 10.1016/s0014-5793(97)01061-2
|View full text |Cite
|
Sign up to set email alerts
|

Selective uptake of high density lipoprotein‐associated cholesterylesters by differentiated Ob1771 adipocytes is modulated by endogenous and exogenous lipoprotein lipase

Abstract: The present study aimed at investigating mechanisms of selective uptake of HDL 3 -associated cholesterylesters (HDL 3 -CEs) by differentiated OM771 adipocytes. Our findings indicate that Obl771 cells are capable of pronounced selective uptake of HDL 3 -CEs in 2.6-fold excess of HDL 3 holoparticle uptake. Selective uptake of HDL 3 -CEs into a releasable pool (presumably located in the cellular plasma membrane) was temperature insensitive while prominent internalization into a non-releasable and subsequent hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 52 publications
(61 reference statements)
0
8
0
1
Order By: Relevance
“…1 and 2) and in vivo (36); therefore, it was suggested that LPL could facilitate transcytosis of lipoprotein-associated vitamins across the BBB (2). This could result either from enhanced LPL-mediated holoparticle transcytosis across the endothelial layer constituting the BBB, or by LPL-mediated selective uptake, as described for HDL-and LDL-associated cholesterol esters (15)(16)(17)37).…”
Section: Discussionmentioning
confidence: 99%
“…1 and 2) and in vivo (36); therefore, it was suggested that LPL could facilitate transcytosis of lipoprotein-associated vitamins across the BBB (2). This could result either from enhanced LPL-mediated holoparticle transcytosis across the endothelial layer constituting the BBB, or by LPL-mediated selective uptake, as described for HDL-and LDL-associated cholesterol esters (15)(16)(17)37).…”
Section: Discussionmentioning
confidence: 99%
“…As yet, there is no physical evidence for such a model. In addition to SR-BI, selective uptake is mediated by lipoprotein lipase (LpL) (19,20), hepatic lipase (21), and apoE in some cells (22) but not others (6). These molecules are proposed to enhance CE transfer by tethering lipoproteins to the cell surface, thereby increasing their effective concentration at sites of selective uptake.…”
mentioning
confidence: 99%
“…CE taken-up selectively characteristically enters a reversible and irreversible compartment, 5,6 and this has been observed in SW872 cells. 8 According to the classical view, the reversible compartment is proposed to include CE that has entered the plasma membrane and remains accessible to extraction by extracellular unlabeled HDL.…”
Section: Resultsmentioning
confidence: 85%
“…3 This implicates an endocytic step in selective uptake and prompted us to examine the role of the LDL receptor-related protein (LRP) 4 in selective uptake, particularly because the LRP binds to apolipoprotein E (apoE), lipoprotein lipase, and hepatic lipase, and these molecules have been shown to facilitate selective uptake. [5][6][7] We found 8 that molecules that interfere with ligand binding to LRP, or reduction of LRP expression using antisense, inhibited HDL-CE selective uptake by human primary adipocytes and SW872 liposarcoma cells by 35% to 50%. These inhibitors included the receptor-associated protein (RAP), which inhibits all ligand binding to the LRP; 4 the polysulfated drug suramin, 9 and 2 ligands of LRP, namely ␣ 2 -macroglobulin (␣ 2 M) and lactoferrin.…”
mentioning
confidence: 99%